2013
DOI: 10.1007/s13721-013-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

Using desolvation energies of structural domains to predict stability of protein complexes

Abstract: Employing domain knowledge for prediction of particular types of protein-protein interactions (PPIs) is a problem that has become increasingly important in the past few years, due to the fundamental role of domains in protein function. We propose a model to predict obligate and non-obligate protein interaction types using desolvation energies of structural domains that are present in the interfaces of protein complexes, which are extracted from the CATH database. The prediction is performed using several state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, if the interactions between the competing proteins and the common protein are weak, they may not cause strong functional implications. Indeed, a number of studies have demonstrated that on the basis of interaction strength, PPIs could be classified into transient or permanent ones 4 36 37 . If two proteins permanently interact with a common protein on the same interface, they may compete more intensively and should be more strictly regulated in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…However, if the interactions between the competing proteins and the common protein are weak, they may not cause strong functional implications. Indeed, a number of studies have demonstrated that on the basis of interaction strength, PPIs could be classified into transient or permanent ones 4 36 37 . If two proteins permanently interact with a common protein on the same interface, they may compete more intensively and should be more strictly regulated in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, recent studies focus on employing domain knowledge to predict protein-protein interactions (PPIs) [4]. There are few domain family resources that can be applied for this purpose such as Pfam and CATH -Class, Architecture, Topology and Homologous superfamily -databases.…”
Section: Introductionmentioning
confidence: 99%